Kierkegaard's Apocalyptic Theology: Temporality, Epistemology and Politics in Practice in Christianity - Baker, Graham (My University, 2011)
This thesis argues for the presence of an apocalyptic theological perspective in Søren Kierkegaard’s Practice in Christianity (1848), one that is of a piece with the apocalypticism that a number of contemporary biblical scholars, theologians and philosophers have located in the letters of the Apostle Paul.
Though familiar motifs (such as the imminent eschaton or the idea of two ages) may be helpful indicators of an apocalyptic theological perspective in a given work, I take the position that apocalyptic theology is fundamentally a matter of settling the question of ultimate lordship or sovereignty. In a Christian context, therefore, where an author manifests a desire to declare the ultimate sovereignty of God (by way of the intervening act of his incarnation in Christ) over and against any worldly counter-claim to sovereignty, he or she partakes of an apocalyptic theology.
I demonstrate that Kierkegaard’s apocalyptic theological perspective is manifested in three ways in Practice in Christianity, namely, with respect to his thinking about temporality, epistemology and politics. The three chapters that make up this thesis take up these themes in turn. In each case, Kierkegaard’s position on these matters is compared with an apocalyptic reading of Paul’s letters. I argue that a concern to declare the ultimate sovereignty of God in these three fundamental areas of human experience is one that Kierkegaard shares with Paul. Insofar as Paul is therefore regarded by his scholarly readers as an apocalypticist, so too, I argue, should Kierkegaard be.
Furthermore, just as the identification of Paul’s apocalypticism is alleged to provide a coherent framework for his gospel, so too, I argue, should Kierkegaard’s apocalypticism be understood as the substratum that informs his theo-philosophical project in Practice in Christianity.
Keywords: Christian theology; 19th century philosophy; Kierkegaard; apocalypticism; political theology; Religious Thought, Theology and Philosophy of Religion; Religious Thought, Theology and Philosophy of Religion